Phylogenetic patterns of ant-fungus associations indicate that farming strategies, not only a superior fungal cultivar, explain the ecological success of leafcutter ants - Mueller, Ulrich G.; Kardish, Melissa R.; Ishak, Heather D.; Wright, April M.; Solomon, Scott E.; Bruschi, Sofia M. [UNESP]; Carlson, Alexis L.; Bacci, Mauricio [UNESP] (Wiley-Blackwell, 2018)
To elucidate fungicultural specializations contributing to ecological dominance of leafcutter ants, we estimate the phylogeny of fungi cultivated by fungus-growing (attine) ants, including fungal cultivars from (i) the entire leafcutter range from southern South America to southern North America, (ii) all higher-attine ant lineages (leafcutting genera Atta, Acromyrmex; nonleafcutting genera Trachymyrmex, Sericomyrmex) and (iii) all lower-attine lineages. Higher-attine fungi form two clades, Clade-A fungi (Leucocoprinus gongylophorus, formerly Attamyces) previously thought to be cultivated only by leafcutter ants, and a sister clade, Clade-B fungi, previously thought to be cultivated only by Trachymyrmex and Sericomyrmex ants. Contradicting this traditional view, we find that (i) leafcutter ants are not specialized to cultivate only Clade-A fungi because some leafcutter species ranging across South America cultivate Clade-B fungi; (ii) Trachymyrmex ants are not specialized to cultivate only Clade-B fungi because some Trachymyrmex species cultivate Clade-A fungi and other Trachymyrmex species cultivate fungi known so far only from lower-attine ants; (iii) in some locations, single higher-attine ant species or closely related cryptic species cultivate both Clade-A and Clade-B fungi; and (iv) ant-fungus co-evolution among higher-attine mutualisms is therefore less specialized than previously thought. Sympatric leafcutter ants can be ecologically dominant when cultivating either Clade-A or Clade-B fungi, sustaining with either cultivar-type huge nests that command large foraging territories; conversely, sympatric Trachymyrmex ants cultivating either Clade-A or Clade-B fungi can be locally abundant without achieving the ecological dominance of leafcutter ants. Ecological dominance of leafcutter ants therefore does not depend primarily on specialized fungiculture of L. gongylophorus (Clade-A), but must derive from ant-fungus synergisms and unique ant adaptations.
Keywords: fungus-growing ant; host-microbe evolution; key innovation; mutualism; symbiosis